A Difference of Past Self-Evaluation Between College Students With Low and High Socioeconomic Status: Evidence From Event-Related Potentials - Zang, Xinlei; Jin, Kaige; Zhang, Feng (Frontiers in Psychology, 2021)
Socioeconomic status (SES) refers to the social position class according to their material and non-material social resources, which is an important factor affecting individual development. We conducted a study with sixty college students as participants to explore whether SES affects past self-evaluation, and used event-related potentials (ERP) in a self-reference task that required participants to judge whether the adjectives (positive or negative) describing themselves five years ago were appropriate for them. Behavioral data showed that individuals' positive past self-evaluation was significantly higher than individuals' negative past self-evaluation, regardless of high or low SES. Individuals with high SES had a significantly higher positive past self-evaluation than those with low SES. ERP data showed that in the low SES group, negative adjectives elicited a marginally greater N400 amplitude than positive adjectives; In the high SES group, negative adjectives elicited a greater LPP amplitude than positive adjectives. N400 is an index of the accessibility of semantic processing, and a larger N400 amplitude reflects less fluent semantic processing. LPP is an index of continuous attention during late processing; the larger LPP amplitude is elicited, the more attention resources are invested. Our results indicated that compared with college students with low SES, the past self-evaluation of college students with high SES were more positive; College students with high SES paid more attention to negative trait adjectives. However, college students with low SES were marginally less fluent in processing negative trait adjectives.